Software Engineering Perspectives and Application in Intelligent Systems Proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016), Vol 2 - Silhavy, Radek; Senkerik, Roman; Oplatkova, Zuzana Kominkova; Silhavy, Petr; Prokopova, Zdenka (Advances in Intelligent Systems and Computing,, 2016)
The volume Software Engineering Perspectives and Application in Intelligent Systems presents new approaches and methods to real-world problems, and in particular, exploratory research that describes novel approaches in the field of Software Engineering. Particular emphasis is laid on modern trends in selected fields of interest. New algorithms or methods in a variety of fields are also presented. The 5th Computer Science On-line Conference (CSOC 2016) is intended to provide an international forum for discussions on the latest research results in all areas related to Computer Science. The addressed topics are the theoretical aspects and applications of Computer Science, Artificial Intelligences, Cybernetics, Automation Control Theory and Software Engineering.